Os processos avaliativos como subsídios ao planejamento institucional: um estudo de caso na Universidade Tecnológica Federal do Paraná - UTFPR - Santos, Cidmar Ortiz dos (2010)
The national evaluation system of higher education has emerged as an important process and that, in an integrated manner, is conducting an assessment of the institutions, courses and student performance, considering the various factors such as social responsibility, system diversity, respect identity, and continuity overall evaluation processes. The system was established by Act 10.861/2004, which regulates the National System off Higher Education Assessment (SINAI). The present study aimed to identify the result obtained in evaluation processes whit background information for planning institutional IES. The methodology used was case study and the data sourc was the Federal Technological University of Paraná, which has an evaluation system implemented. The main findigs are :The system is structured and largely consolidated, part of the actions undertaken by the independent institution of mandatory legislation, are propositions that go beyond legal obligation, also deserves special attention, the mechanisms used, which makes up a whole category by the total assessment of the institution. Keywords: Institutional Planning. Institutional Assessment. Higher Education Institutions. Committee Assessment (CPA). National Systme of Higher Education Assessment (SINAI).